2019
DOI: 10.1002/smll.201905731
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Robust Memristor Enabled by Lead‐Free Double Perovskite for High‐Performance Information Storage

Abstract: Memristors are emerging as a rising star of new computing and information storage techniques. However, the practical applications are severely challenged by their instability toward harsh conditions, including high moisture, high temperatures, fire, ionizing irradiation, and mechanical bending. In this work, for the first time, lead‐free double perovskite Cs2AgBiBr6 is utilized for environmentally robust memristors, enabling highly efficient information storage. The memory performance of the typical indium‐tin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(93 citation statements)
references
References 67 publications
0
93
0
Order By: Relevance
“… 16 Additionally, it has been applied in X-ray detectors 17 and memristors. 18 The optoelectronic properties of Cs 2 AgBiBr 6 stimulated the development of low-dimensional (i.e., 2D) perovskites from their 3D counterparts by the introduction of large A-site cations. These layered double perovskites feature many interesting properties, for example, the transition from an indirect to a direct band gap material by tuning the number of adjacent octahedra layers.…”
mentioning
confidence: 99%
“… 16 Additionally, it has been applied in X-ray detectors 17 and memristors. 18 The optoelectronic properties of Cs 2 AgBiBr 6 stimulated the development of low-dimensional (i.e., 2D) perovskites from their 3D counterparts by the introduction of large A-site cations. These layered double perovskites feature many interesting properties, for example, the transition from an indirect to a direct band gap material by tuning the number of adjacent octahedra layers.…”
mentioning
confidence: 99%
“…[ 135,155–158 ] Recently, Cheng et al reported environmentally robust memristors based on lead‐free double perovskite Cs 2 AgBiBr 6 , which remained robust in harsh environments, including humidity as high as 80%, temperatures up to 180 °C, an alcohol burner flame lasting 10 s, and 60 Co γ‐ray irradiation for a dosage of 5 × 10 5 rad (SI). [ 157 ] This robustness stems from the high formation energy and good crystallinity of Cs 2 AgBiBr 6 . The memristors based on graphene/MoS 2‐ x O x /graphene vdW heterostructures were demonstrated to maintain stable resistive switching at a temperature as high as 340 °C, [ 135 ] which is the highest operating temperature reported so far.…”
Section: Key Requirements and Progress For Large‐scale Memristor Cbasmentioning
confidence: 99%
“…Therefore, they are selected to use in resorbable, degradable, and compatible applications. Furthermore, great efforts have been devoted to exploring new inorganic materials such as perovskite for environmental applications, especially halide perovskite [33,[76][77][78][79][80][81]. Some researches indicate that halide perovskite materials can also be utilized for various applications in terms of environmental protection, for instance, environmental-friendly sensors, disposable consumer devices, and green electronics [77,[80][81][82].…”
Section: Inorganic Thin-film Materialsmentioning
confidence: 99%